The Art of Representation: How Reputation Affects Success with Different Audiences in the Contemporary Art Field - ERTUG, Gokhan (Institutional Knowledge at Singapore Management University, 2016)
We study the effects of actors' audience-specific reputations on their levels of success with different audiences in the same field. Extending recent work that has emphasized the presence of multiple audiences with different concerns, we demonstrate that considering audience specificity leads to an improved understanding of reputation effects. Using data on emerging artists in the field of contemporary art from 2001 to 2010, we investigate the manner in which artists' audience-specific reputations affect their subsequent success with two distinct audiences: museums and galleries. Our findings suggest that audience-specific reputations have systematically different effects with respect to success with museums and galleries. Our findings also illuminate the extent to which audience-specific reputations are relevant for emerging research on the contingent effects of reputation. In particular, our findings support our predictions that audiences differ from one another in terms of the extent to which other signals (specifically, status and interaction with other audiences) enhance or reduce the value of audience-specific reputations. Our study thus advances theory by providing empirical evidence for the value of incorporating audience-specific reputations into the general study of reputation.